Microbial hydroxylation of 17β-estradiol by Penicillium brevicompactum. Issue 4 (3rd July 2016) - Shan, Lihong; Li, Yang; Chen, Yanjie; Yin, Minghui; Huang, Jiajia; Zhang, Zhenzhong; Shi, Xiufang; Liu, Hongmin
Abstract: Microbial hydroxylation of 17β-estradiol (1 ) with Penicillium brevicompactum, a fungal species not used in biotransformation so far, yielded four metabolites: 1, 3, 5-estratriene-3, 15α-diol-17-one (2 ); 1, 3, 5-estratriene-3, 6α, 17β-triol (3 ); 1, 3, 5-estratriene-3, 15α, 17β-triol (4 ); and 1, 3, 5-estratriene-3, 6α, 15α-triol-17-one (5 ). All the products were determined by 1 H NMR, 13 C NMR, two-dimensional NMR, and HRMS techniques. Compounds3, 4, and5 are reported for the first time via microbial transformation, and5 is a new compound as far as we know. Possible metabolic pathway of 17β-estradiol via Penicillium brevicompactum was also proposed.